Metal / molecular sieve ozone catalyst, method for preparing the same, and use thereof
By using a three-dimensional interconnected high-silica molecular sieve support to support metal oxide ozone catalysts, the problems of low catalytic efficiency and poor stability in existing technologies have been solved, achieving efficient treatment of papermaking wastewater that meets national emission standards and simplifying the preparation process.
Patent Information
- Application Number
- CN202611256621.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-19
- Publication Date
- 2026-11-06
AI Technical Summary
Existing heterogeneous ozone catalysts have low efficiency and low stability in catalytic ozone oxidation during papermaking wastewater treatment, failing to meet national wastewater safety discharge standards. Furthermore, their preparation process is complex and costly.
Metal oxides are loaded onto a high-silica molecular sieve carrier with three-dimensional interconnected pores, and metal precursors are loaded by an equal-volume impregnation method to ensure that the active components are uniformly dispersed in the pores and avoid agglomeration. The hydrophobic pores are used to enrich organic pollutants and provide a stable mass transfer network.
It effectively reduced the COD of papermaking wastewater to below 45 mg/L at room temperature. The catalyst showed no significant activity decay after 5 cycles, demonstrating excellent stability and high COD removal rate.
Smart Images

Figure CN123038869A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of catalyst technology, specifically a metal / molecular sieve ozone catalyst, its preparation method, and its application. Background Technology
[0002] Since 2015, my country has promulgated a number of relevant policies, including the Environmental Protection Law, the Environmental Impact Assessment Law of the People's Republic of China, the Water Pollution Prevention and Control Law, the Solid Waste Pollution Prevention and Control Law, the Technical Policy for Pollution Prevention and Control in the Paper Industry, and the Guidelines for Feasible Technologies for Pollution Prevention and Control in the Pulp and Paper Industry. With increasingly stringent requirements for water resource protection, the country's requirements for industrial wastewater discharge will also become more stringent. Therefore, it is not only necessary to optimize papermaking processes, but also to place higher demands on papermaking wastewater treatment technologies to ensure that they meet discharge standards.
[0003] Ozone oxidation is a widely used advanced oxidation process in wastewater treatment. Ozone itself has a high redox potential and can react with most organic matter in water. However, ozone oxidation alone results in low COD removal rates and incomplete mineralization of organic matter, often requiring the addition of heterogeneous catalysts to improve ozone utilization efficiency. Currently, heterogeneous ozone catalysts face two main challenges: firstly, low pollutant conversion rates after catalytic ozone oxidation, failing to meet national wastewater safety discharge standards (below 50 mg / L); and secondly, catalyst stability in complex wastewater environments. Existing widely used heterogeneous ozone catalysts are supported noble metal and transition metal catalysts.
[0004] The invention disclosed in CN114160184A describes the synthesis of silver nanoparticles to prepare a silver-cerium catalyst for synergistic ozone catalytic oxidation of volatile organic compounds (VOCs). The strong interaction between silver and cerium achieves high CO2 selectivity and good stability. However, the preparation process involves multiple steps, including silver nanoparticle synthesis, support treatment and loading, and requires strict control of reaction conditions at each step, such as solution ratio, reaction temperature, and time, which are quite demanding. The use of precious metal catalysts increases the difficulty and cost of preparation.
[0005] CN113856691A discloses a method for preparing an ozone catalyst by loading oxides of various transition metal elements as active components onto a particulate alumina support, which can effectively improve the oxidation effect of treating papermaking wastewater using an ozone catalyst-ozone-hydrogen peroxide process. However, the preparation process involves multiple steps, and the catalyst needs to function in the ozone-hydrogen peroxide process; its effect on treating papermaking wastewater by catalytic ozone oxidation alone is poor. This may be because the active components rely solely on dispersion on the surface of the alumina support, are prone to aggregation under high loading, and in complex water conditions, acidic sites are occupied and deactivated.
[0006] CN120421026A discloses a synergistic ozone catalytic oxidation (VOCs) bimetallic Mn-M / MOR catalyst that can efficiently remove toluene and achieve complete ozone decomposition. The MOR molecular sieve support used is a one-dimensional straight-channel structure with a large size but lacks connecting channels. Reactants and products can only diffuse in a single direction; once the pore openings or interior are blocked by large molecules or carbon deposits, the entire channel becomes deactivated. The testing environment involves adding water vapor to the gas-phase system for water resistance testing, making it difficult to truly simulate the liquid-phase treatment process of actual industrial wastewater.
[0007] In summary, the ozone heterogeneous catalyst used in the advanced treatment process of papermaking wastewater has a relatively low overall catalytic ozone oxidation efficiency and insufficient stability. Furthermore, the catalyst selection process failed to ensure that the active components of the catalyst were compatible with the basic water quality of the wastewater. Summary of the Invention
[0008] (a) Technical problems to be solved In view of the above-mentioned shortcomings and deficiencies of the prior art, the present invention provides a metal / molecular sieve ozone catalyst, which is a molecular sieve support with a three-dimensional interconnected pore topology and high silicon content, loaded with metal oxides, and has high catalytic ozone oxidation efficiency and high stability in papermaking wastewater.
[0009] Accordingly, the present invention also provides the above-mentioned metal / molecular sieve ozone catalyst and its application.
[0010] (II) Technical Solution To achieve the above objectives, the main technical solutions adopted by this invention include: In a first aspect, the present invention provides a method for preparing a metal / molecular sieve ozone catalyst, comprising the following steps: The S1 molecular sieve was first calcined to remove the template agent, and the saturated water absorption was determined; the molecular sieve has a three-dimensional interconnected pore topology and a silicon-aluminum molar ratio ≥100; S2 According to the saturated water absorption capacity, take dry molecular sieve powder and load it onto the molecular sieve by an equal volume impregnation method with an aqueous solution containing a metal precursor; the aqueous solution containing the metal precursor is a combination of at least one of the precursors of iron, copper, and cobalt. After being impregnated with S3, the metal / molecular sieve ozone catalyst is obtained by sequentially undergoing static aging, drying, and a second calcination.
[0011] This invention, based on the application scenario of metal / molecular sieve ozone catalysts in the advanced treatment of papermaking wastewater, firstly discovers that one-dimensional molecular sieves can become clogged at the pore openings or inside the pores. Those skilled in the art have not encountered this technical problem in the application of such catalysts. Based on this technical problem, this invention, for the first time, uses a molecular sieve with three-dimensional interconnected pores as a carrier to solve the clogging problem. Furthermore, this invention discovers that the silicon-to-aluminum ratio of the molecular sieve has a decisive influence on the efficiency and stability of catalytic ozone oxidation in the advanced treatment of papermaking wastewater. Only the hydrophobicity of high-silicon or pure silicon molecular sieves can achieve selective enrichment of organic matter and anti-fouling protection of active sites, making them less prone to loss or aggregation in complex wastewater environments, overcoming the technical prejudice held by those skilled in the art that catalysts must be hydrophilic. Finally, this application, based on the equal-volume impregnation method with precise measurement of saturated water absorption, ensures that the metal precursor solution completely enters the pore interior and spreads uniformly on the pore walls. After calcination, highly uniform nanoscale dispersion of the active components is achieved, fundamentally avoiding surface aggregation.
[0012] The molecular sieve with three-dimensional interconnected pores, high silica content, and equal-volume impregnation method have a synergistic effect on the catalytic effect of the catalyst. Specifically, the hydrophobic channels actively capture and enrich organic pollutants, the three-dimensional interconnected pores provide a smooth mass transfer network and confine and anchor the active components, and the equal-volume impregnation method ensures that the active components are precisely loaded into the aforementioned functional microenvironment. This synergistic combination enables the catalyst to stably reduce the chemical oxygen demand (COD) of actual papermaking wastewater biochemical effluent to below 50 mg / L under ozone conditions alone, and the catalyst exhibits unexpected technical effects such as no significant decline in catalytic activity after more than 5 cycles of recycling.
[0013] To further prevent aggregation, the method of loading the molecular sieve with an aqueous solution containing a metal precursor by equal volume impregnation according to the present invention includes: adding the aqueous solution containing the metal precursor to the molecular sieve in two or more steps.
[0014] Optionally, the molecular sieve is a combination of at least one of the MFI, BEA, and CHA topologies.
[0015] Preferably, the molecular sieve is a pure silicon molecular sieve.
[0016] Optionally, the aqueous solution containing the metal precursor is an aqueous solution of at least one of ferric nitrate nonahydrate, copper nitrate trihydrate, and cobalt nitrate hexahydrate, with a concentration of 0.1 to 0.2 mol / L.
[0017] Optionally, in step S1, the heating rate of the first calcination is 1~5℃ / min, the first calcination temperature is 450~600℃, and the first calcination time is 4~8h.
[0018] Optionally, in step S1, the first calcination heating rate is 2℃ / min, the temperature is 550℃, and the calcination time is 6h. Optionally, in step S3, the static aging time is 12 to 48 hours; the drying temperature is 80 to 120°C. Optionally, the second roasting temperature is 450–600°C, and the time is 2–6 hours.
[0019] Optionally, in step S3, after impregnation with equal volume, the mixture is left to stand at room temperature for 22 hours, dried at 100°C for 2 hours, and then calcined at 550°C for 4 hours.
[0020] Optionally, in step S1, the method for preparing the aqueous solution containing the metal precursor includes: dissolving the soluble salt in deionized water and sonicating it until the solution is clear and transparent; the amount of deionized water added is determined based on the saturated water absorption measured in step S1.
[0021] Optionally, the soluble salt is a solid metal nitrate.
[0022] Optionally, the ultrasound session lasts for 10 to 15 minutes.
[0023] Optionally, the mass of molecular sieve required for the equal volume impregnation method is 1.0~3.0 g, and the water required is 0.5~1.5 g.
[0024] Secondly, the present invention also provides a metal / molecular sieve ozone catalyst prepared by the preparation method described in any of the above embodiments.
[0025] Thirdly, the present invention also provides a metal / molecular sieve ozone catalyst, which uses a molecular sieve support, wherein the pores and surface of the molecular sieve support are loaded with metal oxide active components. The molecular sieve support has a combination of at least one of the topologies MFI, BEA, and CHA, with a silicon-to-aluminum molar ratio greater than or equal to 100 and a grain size of 100–200 nm. The active component of the metal oxide is at least one of oxides of iron, copper, and cobalt; The active metal oxide component is uniformly dispersed on the molecular sieve support.
[0026] Optionally, the metal / molecular sieve ozone catalyst has characteristic diffraction peaks of topological structure and characteristic diffraction peaks of metal oxide in X-ray diffraction pattern, and the characteristic diffraction peaks of metal oxide are broadened.
[0027] Fourthly, the present invention also provides the application of the metal / molecular sieve ozone catalyst described in any of the above embodiments in the deep treatment of papermaking wastewater.
[0028] Optionally, the method of application includes the following steps: under normal temperature, normal pressure and ozone alone conditions, the biochemical effluent of papermaking wastewater to be treated is contacted with the metal / molecular sieve ozone catalyst to perform catalytic ozone oxidation treatment.
[0029] (III) Beneficial Effects
[0030] Compared with existing technologies, the metal / molecular sieve ozone catalyst provided by this invention exhibits a high COD removal rate in the advanced treatment of papermaking wastewater: it can reduce the COD of actual papermaking industrial wastewater to below 45 mg / L at room temperature (below the national safety emission standards). It demonstrates stable performance under the reaction conditions, with no significant decrease in catalytic activity or metal leaching observed after more than five repeated reactions, showcasing excellent lifespan and industrial application potential.
[0031] The molecular sieve selected in this invention utilizes its combination of three-dimensional pore confinement effect and the hydrophobicity of pure silicon. Through the synergistic effect of equal-volume impregnation, the metal / molecular sieve ozone catalyst and the metal oxide active component are uniformly dispersed on the molecular sieve support, exhibiting excellent stability and high COD removal rate.
[0032] It possesses excellent active sites and stability: the confinement effect of the pores facilitates the high dispersion and fixation of active components, and can firmly lock active metal nanoparticles in the pores. In addition, the high-silica molecular sieve is hydrophobic, has strong resistance to organic pollution and metal ion poisoning, and has a stable structure, making it less prone to loss or aggregation in complex wastewater environments.
[0033] It has the ability to control the metal species: the equal volume impregnation method can make the type, loading and size of the metal components controllable and adjustable, so as to meet the needs of different catalytic reaction conditions.
[0034] Pore shape selection and enrichment effect: The three-dimensional pore network of MFI molecular sieves is conducive to molecular diffusion and selective transport. The regular pores can selectively adsorb the main pollutants such as lignin derivatives and aromatic compounds with matching molecular size in papermaking wastewater, concentrating them around the active sites, which greatly improves the local reaction rate and ozone utilization. Attached Figure Description
[0035] Figure 1 XRD phase characterization diagrams for Examples 1-3 and Comparative Example 1; Figure 2 Scanning electron microscope images of the Fe2O3 / MFI and Fe2O3 / MFI(Al) catalysts prepared in Example 1 and Comparative Example 1; Figure 3 The elemental distribution characterization diagrams are for the Fe2O3MFI and Fe2O3 / MFI(Al) catalysts prepared in Example 1 and Comparative Example 1. Figure 4 Diagram of a reaction device for deep treatment of papermaking wastewater by catalytic ozone oxidation; Figure 5 A comparison chart showing the efficiency of catalytic ozone deep treatment of papermaking wastewater with different ozone generation levels; Figure 6 A comparison chart showing the efficiency of catalytic ozone deep treatment of papermaking wastewater at different reaction times; Figure 7 A comparison chart showing the efficiency of deep treatment of papermaking wastewater with catalytic ozone at different pH levels; Figure 8 Comparison of ozone catalytic efficiency between Fe2O3 / MFI, CuO / MFI and CoO / MFI catalysts with 2wt.% metal loading and individual ozone catalysis results; Figure 9 Comparison of ozone catalytic efficiency between Fe2O3 / MFI, CuO / MFI and CoO / MFI catalysts with 5 wt.% metal loading and individual ozone catalysis results; Figure 10 Comparison of ozone catalytic efficiency between Fe2O3 / MFI, CuO / MFI and CoO / MFI catalysts with 8 wt.% metal loading and individual ozone catalysis efficiency; Figure 11 A comparison of the catalytic efficiency of Fe2O3 / MFI catalysts with different metal loadings, 10 wt.% Fe2O3 / MFI (Al), and pure silicon MFI supported catalysts is shown in the figure. Figure 12 The graph shows the stability effect of the Fe2O3 / MFI, CuO / MFI, CoO / MFI and Fe2O3 / MFI (Al) metal-molecular sieve catalysts prepared in Examples 1-3 and Comparative Example 1 on the deep treatment of papermaking wastewater with ozone. Detailed Implementation
[0036] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort. Example 1
[0037] This embodiment provides a method for preparing Fe2O3 / MFI molecular sieve catalyst, the steps of which are as follows: Preparation of S1 and MFI molecular sieve supports: 28.91 g of deionized water was placed in a PP bottle, and 8.864 g of tetrapropylammonium hydroxide (TPAOH) was added. The mixture was stirred at room temperature for 15 min, and then 9.52 g of tetraethyl orthosilicate (TEOS) was added. The mixture was stirred and aged for another 6 h. Then, it was transferred to a reaction vessel and hydrothermally crystallized at 180 °C for 96 h. After removal, deionized water was added and centrifuged until the pH was neutral. The product was then dried in an oven at 80 °C overnight. Subsequently, the obtained solid product was transferred to a muffle furnace and calcined at 550 °C for 6 h to obtain the MFI molecular sieve support. S2. Obtaining the saturated adsorption volume: The molecular sieve support prepared in step S1 was placed in a muffle furnace and calcined in air to remove the template agent from the molecular sieve. A small amount of completely dried molecular sieve powder was taken and deionized water was added dropwise with a dropper while stirring rapidly with a glass rod until all the powder just clumped together and there was no dry powder, but no excess liquid seeped out. The volume of water consumed, V (ml), was recorded. S3. Based on the saturated adsorption volume of step S2, place 1.5g of the MFI molecular sieve support prepared in step S1 in a beaker, dissolve 1.21g of ferric nitrate nonahydrate in 0.116g of deionized water, sonicate at room temperature for 10min, add the metal salt solution to the molecular sieve, stir at room temperature for 5min, and let stand for 22h. Then dry at 100℃ for 6h and calcine at 550℃ for 4h to obtain the Fe2O3 / MFI molecular sieve catalyst. Example 2
[0038] This embodiment provides a catalyst for preparing CuO / MFI with CuO supported on pure silicon MFI using an equal-volume impregnation method.
[0039] Preparation of S1 and MFI molecular sieve supports: 43.36 g of deionized water was placed in a PP bottle, and 13.4 g of tetrapropylammonium hydroxide (TPAOH) was added. The mixture was stirred at room temperature for 15 min, and then 14.28 g of tetraethyl orthosilicate (TEOS) was added. The mixture was stirred and aged for another 6 h. The mixture was then transferred to a reaction vessel and hydrothermally crystallized at 180 °C for 96 h. Afterward, deionized water was added, and the mixture was centrifuged until the pH was neutral. The product was then dried in an oven at 80 °C overnight. The resulting solid product was then transferred to a muffle furnace and calcined at 550 °C for 6 h. This yielded the MFI molecular sieve support. S2. Obtaining the saturated adsorption volume: Same as step S2 in Example 1.
[0040] S3. Place 1g of the MFI molecular sieve prepared in step S1 in a beaker, dissolve 0.331g of copper nitrate trihydrate in 0.132g of deionized water, sonicate at room temperature for 10min, add the metal salt solution to the molecular sieve, stir at room temperature for 5min, and let stand for 22h. Then dry at 100℃ for 6h and calcine at 550℃ for 4h to finally obtain the CuO / MFI molecular sieve catalyst. Example 3
[0041] This embodiment provides a CoO / MFI catalyst for preparing pure silicon MFI supported on metal component CoO using an equal-volume impregnation method.
[0042] S1. Preparation of MFI molecular sieve support: Same as step S1 in Example 1; S2. Obtaining the saturated adsorption volume: Same as step S2 in Example 1; S3. Place 1.5g of MFI molecular sieve obtained in step S1 in a beaker, dissolve 0.392g of cobalt nitrate hexahydrate in 0.2477g of deionized water, sonicate at room temperature for 10min, add the metal salt solution to the molecular sieve, stir at room temperature for 5min, and let stand for 22h. Then dry at 100℃ for 6h and calcine at 550℃ for 4h to finally obtain the CuO / MFI catalyst.
[0043] Comparative Example 1
[0044] This comparative example provides a high-silicon MFI supported metal Fe2O3 Fe2O3 Fe2O3 / MFI catalyst prepared by an equal-volume impregnation method, denoted as: Fe2O3 / MFI(Al) catalyst.
[0045] After obtaining the corresponding saturated adsorption volume using the same method as step S2 in Example 1, 1.5 g of commercial MFI molecular sieve with a silicon-to-aluminum ratio of 100 was placed in a beaker. 1.21 g of ferric nitrate nonahydrate was dissolved in 0.116 g of deionized water, and the mixture was sonicated at room temperature for 5 min. The metal salt solution was then added to the molecular sieve, stirred at room temperature for 5 min, and allowed to stand for 22 h. The mixture was then dried at 100 ℃ for 6 h and calcined at 550 ℃ for 4 h to finally obtain the Fe2O3 / MFI(Al) catalyst.
[0046] Comparative Example 2
[0047] This comparative example provides a method for preparing a pure silicon MFI catalyst, which is the same as step S1 in Example 1, to obtain the corresponding MFI molecular sieve support as a pure silicon MFI catalyst.
[0048] Comparative Example 3 This comparative example provides a high-silicon MFI-supported Fe2O3 / MFI catalyst prepared by an excess impregnation method, the steps of which are as follows: S1, the same as step S1 in Example 1; S2. Prepare excess impregnation solution: Dissolve 1.21g of ferric nitrate nonahydrate in 10mL of deionized water (far exceeding the carrier's saturated water absorption capacity of 0.116mL), and sonicate for 10 minutes until clear and transparent; S3. Immerse 1.5g of pure silicon MFI support in the above excess impregnation solution and let it stand at room temperature for 22h. Then filter off the excess solution and dry the impregnated support at 100℃ for 2h.
[0049] Compared with Example 1, the catalyst of Comparative Example 3 has sharper XRD diffraction peaks (larger grain size), and the elemental distribution diagram shows local enrichment or surface agglomeration of Fe element. It has a lower COD removal rate and more obvious activity decay after 5 cycles.
[0050] It can be seen that different impregnation methods lead to significant differences in the dispersion state and catalytic performance of active components. The equal-volume impregnation method has a significant impact on the COD removal rate and stability.
[0051] Characterization Example 1
[0052] The Fe2O3 / MFI, CuO / MFI, and CoO / MFI catalysts obtained in Examples 1, 2, and 3, as well as the Fe2O3 / MFI (Al) catalyst obtained in Comparative Example 1, were subjected to XRD analysis. The results are as follows: Figure 1 As shown.
[0053] from Figure 1 As can be seen from the XRD phase characterization spectra of Fe2O3 / MFI, CuO / MFI, CoO / MFI and Fe2O3 / MFI(Al) catalysts, the XRD spectra show that metal / molecular sieve catalysts were successfully prepared in Examples 1, 2 and 3. The diffraction peaks of Fe2O3 / MFI, CuO / MFI, CoO / MFI and Fe2O3 / MFI(Al) can be well matched with the diffraction peaks of MFI molecular sieve. Moreover, with the increase of loading, metal diffraction peaks of Fe2O3, CuO and CoO were found, indicating that the metal oxides were successfully loaded.
[0054] Characterization Example 2
[0055] Scanning electron microscopy was performed on the Fe2O3 / MFI and Fe2O3 / MFI(Al) catalysts obtained in Example 1 and Comparative Example 1, and the results are as follows: Figure 2 As shown.
[0056] from Figure 2 It can be seen that Fe2O3 / MFI exhibits a regular and uniform hexagonal structure, with molecular sieve crystal particle sizes ranging from 100 to 200 nm. In contrast, Comparative Example 1 shows an irregular plate-like structure, with molecular sieve crystal particle sizes around 1 μm. Figure 2 The results showed that the metal loading did not affect the morphology and structure of the molecular sieve support.
[0057] Characterization Example 3
[0058] Elemental distribution tests were performed on the Fe₂O₃ / MFI and Fe₂O₃ / MFI (Al) catalysts obtained in Example 1 and Comparative Example 1. The results are as follows: Figure 3 As shown in the figure, the elemental distribution diagram reveals that the Fe element is uniformly distributed in the Fe2O3 / MFI molecular sieve catalyst, while the Fe element distribution in the Fe2O3 / MFI(Al) catalyst is more concentrated, making it prone to aggregation. This indicates that using nano-molecular sieves as a support during the synthesis process results in better metal dispersion and provides more active sites. It also suggests that the pure silicon MFI isovolume impregnation method, while the Fe2O3 / MFI(Al) catalyst with higher aluminum content, is more prone to aggregation.
[0059] Figure 3 The three images at the top are elemental distribution diagrams of Fe2O3 / MFI; Figure 3 The three images in the lower part are elemental distribution diagrams of Fe2O3 / MFI(Al).
[0060] experiment use Figure 4 The fixed-bed reactor shown uses the Fe2O3 / MFI catalyst prepared in Experimental Example 1, with a loading of 1.0 g, placed in the catalyst bed; the wastewater treatment volume is 500 mL. The wastewater being treated is: wastewater from the Qingshan Paper Industry wastewater treatment plant's biochemical effluent and wastewater from the Jianle Jishan Industrial Park. The water quality parameters are shown in Table 1. Table 1 Test water quality parameters
[0061] Experimental Example 1
[0062] The purpose of this experiment is to investigate the effect of ozone generation on the efficiency of deep treatment of papermaking wastewater by catalytic ozone oxidation, and to determine the optimal ozone generation.
[0063] Under normal temperature and pressure conditions, the samples were divided into groups, with each group having different ozone generation rates of 0.25 g / h, 0.75 g / h, 1.0 g / h, 1.5 g / h, 3.0 g / h, and 6.0 g / h. The ozone inlet flow rate was 500 mL / min. The ozone was generated by the ozone generator and introduced into the wastewater to be tested. Samples were taken every 10 minutes during the reaction, and the COD removal rate was determined using the dichromate method (HJ828-2017).
[0064] Experimental results are as follows Figure 5As shown, the COD removal rate was significantly higher when the ozone generation rate was 0.75 g / h compared to ozone generation rates of 0 and 0.25 g / h. Further increasing the ozone generation rate slowed the increase in COD removal rate. This is because: initially, the wastewater contains no ozone, so ozone will penetrate into the liquid phase due to the concentration difference; as the ozone generation rate increases, the ozone concentration in the liquid phase also increases, and subsequently, the ozone in the wastewater gradually becomes saturated, causing the COD removal rate to begin to slow down. Most organic pollutants in wastewater are difficult to degrade. Even when the ozone generation rate is adjusted to 3 and 6 g / h, the generated ·OH groups are unlikely to rapidly degrade large organic molecules into smaller molecules or completely mineralize them in a short time. Prolonged high concentrations of ozone can be dangerous; therefore, 1.5 g / h was chosen as the optimal ozone generation rate.
[0065] Experimental Example 2
[0066] The purpose of this experiment is to investigate the effect of reaction time on the efficiency of deep treatment of papermaking wastewater by catalytic ozone oxidation and to determine the optimal reaction time.
[0067] Under normal temperature and pressure conditions, the ozone generation rate was set at 1.5 g / h (the optimal value determined in Experiment 1), the ozone concentration at 50 mg / L, and the ozone inlet flow rate at 500 mL / min. Samples were taken at 10 min, 20 min, 30 min, 40 min, 60 min, 90 min, and 120 min of the reaction, and the COD removal rate was determined and calculated using the dichromate method (HJ828-2017).
[0068] from Figure 6 The results show that the COD removal rate initially increases rapidly and then slows down with increasing reaction time. According to chemical reaction kinetics, the reaction rate is directly related to the substrate concentration. In this study, the substrates were water-soluble ozone and its activation product ·OH, and organic pollutants. When ozone was saturated, the factor affecting the reaction rate was the concentration of organic pollutants that could react with ozone and its activation product ·OH. As the reaction time increased, the concentration of these organic pollutants gradually decreased, thus slowing the reaction rate compared to the initial stage of the experiment. After 60 minutes, the rate of slowdown was very small, indicating that ozone catalysis had reached a critical value. Therefore, 60 minutes was selected as the optimal reaction time.
[0069] Experimental Example 3
[0070] The purpose of this experiment is to investigate the effect of the initial pH value of wastewater on the efficiency of deep treatment of papermaking wastewater by catalytic ozone oxidation, and to determine the optimal pH conditions.
[0071] Water quality: Initial COD is 120±5 mg / L, and the pH of the raw water is 7.5±0.5. The wastewater treatment volume is 500 mL.
[0072] The initial pH of the wastewater was adjusted using 1 mol / L sodium hydroxide solution and 1 mol / L sulfuric acid solution, with initial pH values set to 2, 3, 4, 5, 6, 7, 8, 9, and 10 for each group. Under normal temperature and pressure conditions, the ozone generation rate was set to 1.5 g / h, the ozone concentration to 50 mg / L, and the ozone inlet flow rate to 500 mL / min. Samples were taken after 60 min of reaction under each condition, and the COD of the effluent was determined using the dichromate method (HJ828-2017), and the COD removal rate was calculated.
[0073] Experimental results are as follows Figure 7 As shown: When the pH value is below 4, the decomposition of ozone molecules in aqueous solution is negligible. The reaction mainly involves the direct reaction between ozone molecules dissolved in wastewater and organic pollutants, resulting in low reaction efficiency. With increasing pH, the COD removal rate of ozone in wastewater gradually increases, primarily due to the accelerated rate of ozone decomposition to form ·OH, which triggers a free radical chain reaction, accelerating organic matter degradation and reducing COD. When the pH in the reactor is greater than 8, the COD removal rate gradually decreases, possibly because the increased pH reduces ozone solubility, leading to excessive ·OH formation and accelerated quenching of ozone itself. The ozone and ·OH are then depleted, thus reducing the COD removal rate. The highest COD removal rate is achieved at pH 8. Considering that the original wastewater pH is close to the optimal pH and the removal efficiency is not significantly different, and considering subsequent discharge issues, the original wastewater pH was chosen for subsequent treatment.
[0074] Test Example 1
[0075] Test objective: To compare the efficiency of ozone oxidation for deep treatment of papermaking wastewater under the same conditions using ozone alone as a catalyst, the metal / molecular sieve ozone catalysts prepared in Examples 1-3 of this invention, and Comparative Examples 1-2, as well as a series of catalysts with different metal loadings, under small-scale laboratory conditions.
[0076] The testing method is as follows: Adopting such Figure 4 The fixed-bed ozone reactor shown is illustrated. Following Examples 1, 2, and 3, Fe₂O₃ / MFI, CuO / MFI, and CoO / MFI catalysts with metal loadings of 2 wt.%, 5 wt.%, 8 wt.%, 10 wt.%, and 12 wt.%, respectively, were prepared by adjusting the concentration of the metal precursor-containing aqueous solution in step S3. The Fe₂O₃ / MFI (Al) with a metal loading of 10 wt.% prepared in Comparative Example 1 and Comparative Example 2 (pure silicon MFI support) were used as catalysts for comparative testing.
[0077] The specific test conditions are as follows: (e.g.) Figure 4The fixed ozone reactor was set up and operated at ambient temperature and pressure. The ozone dosage was 1.5 g / h, the ozone concentration was 50 mg / L, and the ozone inlet flow rate was 500 mL / min. 1.0 g of catalyst was placed in the catalyst bed. Ozone was generated by an ozone generator and introduced into the wastewater (500 ml) to be reacted via an aeration device. The exhaust gas was absorbed by a KI solution. Samples were taken every 10 minutes. The COD of the wastewater was determined using the dichromate method (HJ828-2017).
[0078] The results are as follows Figure 8-11 As shown, the Fe2O3 / MFI with a metal loading of 10 wt.% exhibited the best catalytic performance throughout the entire test process, with a COD removal rate that remained stable at 60%~70%, an ozone utilization rate that remained stable between 1.2 and 1.7, and an effluent COD that remained below 45 mg / L.
[0079] Figure 8-11 In the middle, 2wt.%, 5wt.%, 8wt.%, 10wt.%, and 12wt.% Fe2O3 / MFI were labeled as (2%)Fe / S-1, (5%)Fe / S-1, (8%)Fe / S-1, (10%)Fe / S-1, and (12%)Fe / S-1, respectively; 2 wt.%, 5 wt.%, and 8 wt.% CuO / MFI were labeled as (2%) Cu / S-1, (5%) Cu / S-1, and (8%) Cu / S-1, respectively; 2 wt.%, 5 wt.%, and 8 wt.% CoO / MFI were labeled as (2%) Co / S-1, (5%) Co / S-1, and (8%) Co / S-1, respectively; Fe2O3 / MFI(Al) with a metal loading of 10 wt.% is labeled as: (10%)Fe / Z-1.
[0080] Comparative Example 2 (pure silicon MFI carrier) is labeled as: pure S-1.
[0081] Test Example 2
[0082] The purpose of this test is to examine the stability of the catalysts prepared in Examples 1-3 and Comparative Example 1 for recycling in the deep treatment of papermaking wastewater by catalytic ozone oxidation.
[0083] The specific test conditions were the same as in Test Example 1. 1.0 g each of the catalysts from Example 1 (Fe₂O₃ / MFI), Example 2 (CuO / MFI), Example 3 (CoO / MFI), and Comparative Example 1 (Fe₂O₃ / MFI(Al)) were taken and subjected to a catalytic ozone oxidation reaction under the same conditions as in Test Example 1. The reaction conditions were: ambient temperature and pressure; wastewater was effluent from a secondary sedimentation tank of a paper mill (COD 120±5 mg / L, pH 7.1±0.5); wastewater treatment volume 500 mL; ozone generation rate 1.5 g / h; ozone concentration 50 mg / L; ozone inlet flow rate 500 mL / min; and reaction time 60 min. After each reaction, the catalyst was removed from the reactor, washed three times with deionized water, dried at 100℃ for 2 h, and the next reaction was carried out under the same conditions. This cycle was repeated five times.
[0084] After each reaction, samples were taken, and the COD of the effluent was determined using the dichromate method (HJ828-2017) to calculate the COD removal rate. The activity retention rate for each cycle was calculated based on the COD removal rate of the first reaction (100%).
[0085] Experimental results are as follows Figure 12 As shown. From Figure 12 It can be seen that the metal / molecular sieve catalysts prepared by the medium-volume impregnation method in Examples 1-3 can stably run more than 5 times in the catalytic ozone deep treatment of papermaking wastewater reaction with almost no performance degradation, indicating that the confinement effect of molecular sieve on metal species and the hydrophobicity of high-silica molecular sieve endow them with excellent catalytic activity and stability.
[0086] In addition, experiments have shown that not all impregnation methods can achieve the technical effects of this invention. The equal-volume impregnation method is a necessary technical means to achieve high dispersion of active components on pure silicon MFI carriers.
[0087] Example 1 shows similar COD removal rates under ozone alone and under a combination of ozone and hydrogen peroxide, demonstrating that the catalyst of this invention is independent of hydrogen peroxide and can achieve the same depth of treatment effect under a simplified process. The alumina-supported iron oxide catalyst performs significantly worse than Example 1 under ozone alone, demonstrating the structural advantages of the catalyst of this invention. Even under its optimal ozone-hydrogen peroxide synergistic conditions, the stability of the alumina-supported iron oxide catalyst is still lower than the COD removal rate of Example 1 under ozone alone.
[0088] In Examples 1-3, the change in the silica-alumina ratio of the molecular sieve has a significant nonlinear effect on the catalytic performance; and the degree of this effect is not taught in the prior art and cannot be reasonably predicted by those skilled in the art; a silica-alumina ratio ≥100 is the critical range for producing significant technical effects; the establishment of this numerical range is the result of the inventor's creative labor through a large number of experimental screenings.
[0089] The catalysts in Examples 1-3 of this invention exhibited extremely low leaching amounts of active components, which is direct quantitative evidence of the three-dimensional interconnected pore confinement effect. The metal leaching amounts of Comparative Example 1 and the alumina-supported iron oxide catalyst were significantly higher than those in Example 1, demonstrating that the pure silicon support and the equal-volume impregnation method make significant contributions to the stable anchoring of the active components.
[0090] The catalysts in Examples 1-3 of this invention not only exhibit excellent COD removal rates, but also show significant improvements in multiple indicators of water quality after treatment.
[0091] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a metal / molecular sieve ozone catalyst, characterized in that, Includes the following steps: The S1 molecular sieve was first calcined to remove the template agent, and the saturated water absorption was determined; the molecular sieve has a three-dimensional interconnected pore topology and a silicon-aluminum molar ratio ≥100; S2 According to the saturated water absorption, take dry molecular sieve powder and load the molecular sieve by an equal volume impregnation method with an aqueous solution containing a metal precursor; the aqueous solution containing the metal precursor is a combination of at least one of iron, copper and cobalt precursors. After being impregnated with S3, the metal / molecular sieve ozone catalyst is obtained by sequentially undergoing static aging, drying, and a second calcination.
2. The preparation method of the metal / molecular sieve ozone catalyst as described in claim 1, characterized in that: The molecular sieve is a combination of at least one of the MFI, BEA, and CHA topologies; Optionally, in step S2, the molecular sieve is subjected to an equal-volume impregnation loading treatment by adding an aqueous solution containing a metal precursor in two or more steps.
3. The method for preparing the metal / molecular sieve ozone catalyst according to claim 1, characterized in that: The molecular sieve carrier is a pure silicon molecular sieve.
4. The method for preparing the metal / molecular sieve ozone catalyst according to claim 1, characterized in that: The aqueous solution containing the metal precursor is an aqueous solution of at least one of ferric nitrate nonahydrate, copper nitrate trihydrate, and cobalt nitrate hexahydrate, with a concentration of 0.1–0.2 mol / L.
5. The method for preparing the metal / molecular sieve ozone catalyst according to claim 1, characterized in that, In step S1, the heating rate of the first calcination is 1~5℃ / min, the first calcination temperature is 450~600℃, and the first calcination time is 4~8h.
6. A metal / molecular sieve ozone catalyst prepared by the preparation method according to any one of claims 1-5.
7. A metal / molecular sieve ozone catalyst, characterized in that: It uses a molecular sieve as a carrier, and the channels and surface of the molecular sieve are loaded with active metal oxide components. The molecular sieve has a combination of at least one of the topologies MFI, BEA, and CHA, a silicon-aluminum molar ratio greater than or equal to 100, and a grain size of 100–200 nm. The active component of the metal oxide is at least one of oxides of iron, copper, and cobalt; The active metal oxide component is uniformly dispersed on the molecular sieve.
8. The metal / molecular sieve ozone catalyst according to claim 7, characterized in that: In its X-ray diffraction pattern, it exhibits characteristic diffraction peaks of topological structure and characteristic diffraction peaks of metal oxide, and the characteristic diffraction peaks of the metal oxide exhibit a broadened morphology.
9. The application of the metal / molecular sieve ozone catalyst according to any one of claims 7-8 in the advanced treatment of papermaking wastewater.
10. The application according to claim 9, characterized in that, The method includes the following steps: under normal temperature, normal pressure and ozone alone conditions, the biochemical effluent of the papermaking wastewater to be treated is contacted with the metal / molecular sieve ozone catalyst to carry out catalytic ozone oxidation treatment.
Citation Information
Patent Citations
Ozone catalyst and preparation method thereof
CN113856691A
Preparation method and application of silver-cerium bimetallic molecular sieve catalyst cooperating with ozone to catalytically oxidize VOCs (Volatile Organic Compounds)
CN114160184A
Bimetal water-resistant catalyst for catalytic oxidation of VOCs at normal temperature in cooperation with ozone and preparation method thereof
CN120421026A
